Pentaquark implications for exotic mesons - Burns, T; Close, F; Dudek, J (2005)
If the exotic baryon Θ +(1540) is a correlated ududs̄ with J P = 1 +/2, then there should exist an exotic meson υ + with strangeness +2, J P = 1 -, mass ∼1.6 GeV, decaying to K + K 0 with width O(10-100) MeV. The π 1(1400; 1600) may be broad members of 10 ± 10 in such a picture, and it is possible that vector mesons in the 1.4-1.7 GeV mass range are related to this multiplet. We suggest that dynamical correlations may limit the spectrum of J P(C) such that the 1 -(±) states are isolated. © 2005 The American Physical Society.